CARICOM single market & economy (Antigua & Barbuda. Ministry of Finance & Economy (Industry & Commerce). CSME Unit St. John'sAG, 2004)
Highlights the various tenets of the CSME and enunciates the Goverment of Antigua and Barbuda's policy towards the new regime.
Keywords: REGIONAL INTEGRATION